Search Computing: Challenges and Directions - Ceri, Stefano; Brambilla, Marco (Lecture Notes in Computer Science, 2010)
Containing detailed papers on search computing, this book includes some visionary contributions on the latest trends and explores the background and related technologies. The papers are written by leading scientists and contain the latest results in the field.